Emergency brain imaging findings in children with first afebril convulsion - Gül Demet Kaya OZCORA; Gonca BEKTAŞ (My University, 2022)
Convulsion is the most common neurological disease seen in childhood and constitutes 4-10% of all neurological diseases and 2% of the admissions to child emergency rooms. While the primary purpose of performing emergency neuroimaging in a child presenting with the first afebrile convulsion is to investigate intracranial pathologies that may require urgent intervention. The cranial imaging to be performed for this purpose are transfontanellar ultrasonography, computed tomography, and magnetic resonance imaging. We aimed to evaluate the necessity, the contribution to diagnosis, and the effect of treatment of magnetic resonance imaging that was performed in the emergency rooms. Patients who were admitted to the pediatric emergency room for a one-year complaint of their first afebrile convulsion and performed brain magnetic resonance imaging in the pediatric emergency room within the first 24 hours of hospital admission were evaluated retrospectively. A statistically significant correlation was found between the abnormal magnetic resonance imaging and abnormal physical examination of the patients (p<0.001). By the brain magnetic resonance imaging findings acute changes were made in the treatment of 7 cases (1.3%) There was no statistically significant relationship between the magnetic resonance imaging abnormality and emergency seizures. We determined that it would be more appropriate to perform magnetic resonance imaging in outpatient clinics in cases where transportation can be provided early, in cases above 6 years of age without risk factors, and have a normal examination. Nonetheless, higher magnetic resonance imaging rates lead to lower computed tomography rates and ıts beneficial for pediatric patients in limiting radiation and providing definitive structural imaging for seizures.
Keywords: Nörolojik Bilimler; Acil Tıp; Temel Sağlık Hizmetleri; Pediatri